1996
DOI: 10.7326/0003-4819-125-5-199609010-00003
|View full text |Cite
|
Sign up to set email alerts
|

A Prognostic Model for Predicting 10-Year Survival in Patients with Primary Melanoma

Abstract: A prognostic model that uses four readily accessible variables more accurately predicts outcome in patients with primary melanoma than does tumor thickness alone. This four-variable model can identify patients at high risk for the recurrence of disease, an identification that becomes increasingly important as adjuvant therapies are developed for treatment of melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
93
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 176 publications
(102 citation statements)
references
References 0 publications
5
93
0
4
Order By: Relevance
“…In order to illustrate the risk data, the results from the Cox regression without significant interactions are presented 6 showing the prognostic impact (percentage of model χ 2 ) for each variable and also the relative importance for each category.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to illustrate the risk data, the results from the Cox regression without significant interactions are presented 6 showing the prognostic impact (percentage of model χ 2 ) for each variable and also the relative importance for each category.…”
Section: Discussionmentioning
confidence: 99%
“…(1) Mervic suggests that adding sex, age and tumour site to the AJCCclassification could improve the prediction of an individual patient's prognosis compared to the AJCC staging system currently in use (1,2). A few prognostic instruments have been presented but some are based on a limited number of patients and others are based on selected groups of patients referred to major institutions treating CMM (3)(4)(5)(6)(7)(8)(9). Hence, former instruments have not been as generalizable as expected.…”
Section: Introductionmentioning
confidence: 99%
“…and W.H. Clark Jr, MD) without knowledge of patients' outcomes [8]. Attributes included Breslow thickness; Clark level, dermal mitotic rate (MR), expressed in terms of mitoses per square millimeter; VGP tumor infiltrating lymphocytes (TIL), classified as either brisk, nonbrisk, or absent; regression, if present in the invasive or in situ radial growth phase adjacent to the VGP; microscopic satellites; ulceration; and vascular (blood or lymphatic) invasion.…”
Section: Pathology Definitionsmentioning
confidence: 99%
“…In contrast, LI had been detected in only a few melanomas on a formal review of hematoxylin and eosin (H&E) stained lesions that included a protocol-specified search for lymphatic and blood vessel invasion [8]. We also found that apparent LI detected by podoplanin immunostaining alone often appeared as single or only a few cells in lymphatic channels and that these cells were often difficult to distinguish from such non-neoplastic cells as histiocytes/ monocytes, lymphocytes or even plump lymphatic endothelial cells within the lymphatic channels.…”
Section: Introductionmentioning
confidence: 99%
“…28,29 In this current study, Breslow thickness again appears to be a strong prognosticator. Obviously, patients with a thinner melanoma have a greater chance of remaining disease free for at least 3 years than those with a thick melanoma (Ͼ 4.0 mm).…”
Section: Discussionmentioning
confidence: 89%